Access Barriers to Dental Health Care in Children with Disability. A Questionnaire Study of Parents. Issue 2 (5th March 2015) - Gerreth, Karolina; Borysewicz‐Lewicka, Maria
Abstract : Background: A patient's with disability everyday life is rife with many limitations such as architectural, transport, information as well as medical, psychological, legal, economic and social barriers. The aim of this study was to evaluate access to dental health care of special‐care schoolchildren with intellectual disability on the basis of their parents' opinion. Material and method: A questionnaire survey was carried out among 264 parents/caregivers of children from eight special‐care schools in Poznan (Poland). Close‐ended questions concerned children's barriers in access to dental care and parents' satisfaction with their children's dental care. Results: Only 31.8% parents/caregivers did not have any problems with access to dental care and the most commonly reported barrier to obtaining dental care was protracted waiting time for a visit (36.7%). Most commonly, children were treated in dental surgery conditions (90.1%). Only 42.1% respondents were satisfied with their children's dental care. Conclusions: The research revealed that there is a need to improve the access of children with disability to dental care. Hence, it seems to be beneficial to set up specialist dental surgeries in special‐care schools which would improve the access of children with disability to prophylaxis as well as dental treatment.